Dynamic susceptibility of spin-1/2 Ising chain in transverse field - Derzhko, O.; Krokhmalskii, T. (Физика низких температур, 1997)
Dynamic susceptibility of the one-dimensional spin-1/2 transverse Ising model is obtained by using the numerical approach suggested earlier [Ferroelectrics 153, 55 (1996)]. The dependence of the susceptibility frequency shapes on the value of the transverse field at various temperatures is discussed. The way in which the frequency shape rebuilds as the transverse field increases is illustrated.